2020
DOI: 10.7150/ijms.50248
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression profile of Lacrimal Glands in rabbit autoimmune dacryoadenitis model

Abstract: Purpose: To identify the differential expression of microRNAs (miRs) and the related gene networks and signal pathways in lacrimal glands (LGs) of rabbit autoimmune dacryoadenitis. Methods: Autoimmune dacryoadenitis in rabbits was induced by transferring activated peripheral blood lymphocytes (PBLs). The LGs of normal and model group rabbits were collected for small RNA sequencing. The most differentially expressed miRs were validated by quantitative real time-polymerase chain reaction (qRT-PCR). Further, bioi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…However, other studies have found miR-150-5p to be elevated in SS patients' saliva, minor SG (69), and serum (70) (Table 3), consistent with the increased expression in male NOD mice tears. miR-150-5p was previously found to be significantly upregulated in a rabbit autoimmune dry eye model investigating differential expression of miRNAs in LG (71). This may be related to the observed upregulation of miR-150-5p in NOD mouse tears, as the LG is the primary source of tears.…”
Section: Discussionmentioning
confidence: 82%
“…However, other studies have found miR-150-5p to be elevated in SS patients' saliva, minor SG (69), and serum (70) (Table 3), consistent with the increased expression in male NOD mice tears. miR-150-5p was previously found to be significantly upregulated in a rabbit autoimmune dry eye model investigating differential expression of miRNAs in LG (71). This may be related to the observed upregulation of miR-150-5p in NOD mouse tears, as the LG is the primary source of tears.…”
Section: Discussionmentioning
confidence: 82%